Cu2+‐selective naked‐eye 'off–on' fluorescent probe with multisignals: chromaticity, fluorescence, electrochemistry. (21st May 2020) - Xu, Xiuling; Zhang, Xiaoli; Cao, Cuilan; Zheng, Bingbing; Deng, Hongxia; Shuai, Qi
Abstract: In this study, a rhodamine–acetylferrocene conjugate of RBFc was synthesized and then characterized using spectroscopy and single‐crystal analysis. The chemosensor RBFc exhibited a marked colour change from colourless to pink after binding to Cu 2+ ions. Importantly, under the presence of the other competing cations in aqueous solution, only Cu 2+ ions caused spirolactam ring opening in rhodamine B in RBFc, resulting in an enhanced absorbance of ultraviolet light spectra and fluorescence spectra, as well as obvious shifts in cyclic voltammetry curves and differential pulsed voltammetry curves. The novel probe described in this manuscript provides an attractive approach for detecting Cu 2+ in the presence of other multisignals.